Pregnancy period and early-life risk factors for inflammatory bowel disease: a Northern Finland birth cohort 1966 study - Timo M. Blomster; Olli-Pekka Koivurova; Ritva Koskela; Karl-Heinz Herzig; Nicholas J. Talley; Jukka Ronkainen (BMC, 2024)
Abstract Background The pathogenesis of inflammatory bowel disease (IBD) has not been fully elucidated. The aim of this study was to analyze the pregnancy period, perinatal period, and infancy period risk factors for IBD in a well-characterized birth cohort from Northern Finland. Methods The Northern Finland Birth Cohort 1966 (NFBC1966) population comprises mothers living in the two northernmost provinces of Finland, Oulu, and Lapland, with dates of delivery between Jan 1st and Dec 31st, 1966 (12 055 mothers, 12 058 live-born children, 96.3% of all births during 1966). IBD patients were identified using hospital registries (from 1966 to 2020) and Social Insurance Institution (SII) registry reimbursement data for IBD drugs (from 1978 to 2016). The data were analyzed by Fisher's exact test and logistic regression. Results In total, 6972 individuals provided informed consent for the use of combined SII and hospital registry data. Of those, 154 (2.1%) had IBD (113 [1.6%] had ulcerative colitis (UC), and 41 (0.6%) had Crohn's disease (CD)). According to multivariate analysis, maternal smoking > 10 cigarettes/day during pregnancy was associated with a nearly 6-fold increased risk of CD in the offspring (OR 5.78, 95% CI 1.70-17.3). Breastfeeding (OR = 0.18, 95% CI 0.08-0.44) and iron supplementation during the first year of life (OR = 0.43, 95% CI 0.21-0.89) were negatively associated with CD. Conclusions Smoking during pregnancy was associated with the risk of CD while Breastfeeding and oral iron supplementation at infancy were negatively associated with the risk of CD later in life.